Validation of Mortality Data Sources Compared to the National Death Index in the Healthcare Integrated Research Database - Jamal-Allial A; Sponholtz T; Vojjala SK; Paullin M; Papazian A; Eshete B; Mahmoudpour SH; Verpillat P; Beachler DC (Pragmatic and Observational Research)
Aziza Jamal-Allial,1 Todd Sponholtz,1 Shiva K Vojjala,2 Mark Paullin,2 Anahit Papazian,1 Biruk Eshete,2 Seyed Hamidreza Mahmoudpour,3 Patrice Verpillat,3 Daniel C Beachler2 1Safety & Epidemiology, Carelon Research, Newton, MA, USA; 2Safety & Epidemiology, Carelon Research, Wilmington, DE, USA; 3Merck Healthcare KGaA, Darmstadt, GermanyCorrespondence: Daniel C Beachler, Carelon Research, 123 Justison Street, Suite 200, Wilmington, DE, 19801, USA, Email Daniel.beachler@carelon.comBackground: The National Death Index (NDI) is the gold standard for mortality data in the United States (US) but has a time lag and can be operationally intensive. This validation study assesses the accuracy of various mortality data sources with the NDI.Methods: This validation study is a secondary analysis of an advanced cancer cohort in the US between January 2010 and December 2018, with an established NDI linkage. Mortality data sources, inpatient discharge, disenrollment, death master file (DMF), Center for Medicare and Medicaid Services (CMS), Utilization management data (U.M.), and online obituary data were compared to NDI.Results: Among 40,692 patients, 25,761 (63.3%) had a death date using NDI; the composite algorithm had a sensitivity of 88.9% (95% CI = 88.5%, 89.3%), specificity was 89.1% (95% CI = 88.6%, 89.6%). At the same time, positive predictive value (PPV) was 93.4% (95% CI = 93.1%, 93.7%), negative predictive value (NPV) was 82.3% (95% CI = 81.7%, 82.9%), and when comparing each individual source, each had a high PPV but limited sensitivity.Conclusion: The composite algorithm was demonstrated to be a sensitive and precise measure of mortality, while individual database sources were accurate but had limited sensitivity.Plain Language Summary: What is known on this topic:The National Death Index (NDI) is the gold standard for ascertaining death in the US, with several limitations, such as time lag and population restrictions.What this study adds:A composite mortality algorithm of several sources of death was shown to be a sensitive and precise in death ascertainment compared to the NDI.Individual mortality sources, such as the Social Security Death Master File and online obituaries, had limited sensitivity on their own compared to the NDI.Keywords: mortality, validation, National Death Index, real word evidence, obituary, claims